Molecular breast imaging detected invasive lobular carcinoma in dense breasts: A case report. Issue 3 (28th January 2019) - Samreen, Naziya; Hunt, Katie N.; Hruska, Carrie B.; Rhodes, Deborah J.
Key Clinical Message: This case highlights the role of molecular breast imaging (MBI) in evaluating persistent clinical concerns after a negative diagnostic mammogram and ultrasound. MBI is especially useful in the diagnosis of invasive lobular carcinoma due to its occult nature on conventional imaging modalities. Abstract : This case highlights the role of molecular breast imaging (MBI) in evaluating persistent clinical concerns after a negative diagnostic mammogram and ultrasound. MBI is especially useful in the diagnosis of invasive lobular carcinoma due to its occult nature on conventional imaging modalities.